Problematika Penghafal Al-Qur’an dalam Pembelajaran Bahasa Arab - Riskiyatul Hasanah; Luthfatul Qibtiyah; Athifah; Izzat Amini (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
This article aims to describe the problems of memorizing the Alquran (Hafidhah) in arabic learning. The approach used in this research is qualitative with a descriptive type. The data collection methods used were observation and interviews. The informants are the homeroom teacher of class 3 B of Ma'had Tahfidh Qur'an Middle School, Putri Al-Amien Prenduan, as well as the Arabic language teacher in class 3 B of Ma'had Tahfidh Qur'an Middle School, Putri Al-Amien Prenduan, and students of class 3 B of SMP Ma'had Tahfidh Qur'an Putri Al-Amien Prenduan. Next, the data obtained was analyzed using the Miles and Huberman model. Meanwhile, to check the validity of data, source triangulation was used. The results of this research are the problems of memorizing the Alquran (Hafidhah) in learning Arabic in takallum, namely lack of mastery of mufrodat, and confusion in using dhomir. To overcome this problem, Arabic teachers make efforts, namely repeating lesson that has been studied and inviting them to speak directly before the lesson begins.